2010
DOI: 10.1108/30905661080001359
|View full text |Cite
|
Sign up to set email alerts
|

How price image dimensions influence shopping intentions for different store formats

Abstract: Purpose -The purpose of this paper is to analyse how five price image dimensions influence shopping intentions for different store formats. Design/methodology/approach -In total, 306 espondents evaluated three stores from a list of 18 retailers on a multiple-item scale, resulting in 918 price-image measurements. Based on these data, a covariance structure analysis in Mplus analyses the direct and indirect impact of five price image dimensions on shopping intentions. A multiple group analysis identifies differe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
70
0
41

Year Published

2012
2012
2016
2016

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 51 publications
(114 citation statements)
references
References 67 publications
3
70
0
41
Order By: Relevance
“…First, while price convenience is an inherent feature of a single price, price processibility and complexity are context-dependent. Price processibility is dependent on the context in which the price is displayed, like shelf layout or unit prices (Zielke 2010). The construct of price complexity refers to price plans consisting of multiple price elements and is dependent on the number of these elements as well as the presence of different numbers and the difficulty of calculations necessary to arrive at a final price (Homburg et al 2014).…”
Section: Conceptualizing Convenience and Convenience Consciousnessmentioning
confidence: 99%
See 1 more Smart Citation
“…First, while price convenience is an inherent feature of a single price, price processibility and complexity are context-dependent. Price processibility is dependent on the context in which the price is displayed, like shelf layout or unit prices (Zielke 2010). The construct of price complexity refers to price plans consisting of multiple price elements and is dependent on the number of these elements as well as the presence of different numbers and the difficulty of calculations necessary to arrive at a final price (Homburg et al 2014).…”
Section: Conceptualizing Convenience and Convenience Consciousnessmentioning
confidence: 99%
“…In this regard price convenience must be distinguished from the related yet clearly discriminable constructs of price processibility (Zielke 2010) and price complexity (Homburg et al 2014). First, while price convenience is an inherent feature of a single price, price processibility and complexity are context-dependent.…”
Section: Conceptualizing Convenience and Convenience Consciousnessmentioning
confidence: 99%
“…So, as hypothesized, the influence of the two independent variables on the dependent one is both direct and indirect via the mediating effect of perceived risk toward SBs (partial mediation model). Store image and SB price-image are correlated as some previous research showed that price-image and store image are two constructs distinct, but quite strongly related (Martineau, 1958;Zielke, 2010).…”
Section: Sb Price-image-perceived Risk Toward Sbs And/or Sb Purchase mentioning
confidence: 79%
“…Price-image perceptions are considered as a part of a retailer's store image (Lindquist, 1974) but the two concepts are different (Zielke, 2010). To the best of our knowledge, SB price-image has not yet been defined in previous research.…”
Section: Sb Price-image-perceived Risk Toward Sbs And/or Sb Purchase mentioning
confidence: 96%
“…As discussed before, perceived value is directly related to quality perception, which is impacted by both intrinsic and extrinsic attributes (Yeung & Soman, 2007;Zielke, 2010). Thus, in order to investigate which attributes are more relevant for perceived quality and, consequently, for the purchase decision process of the respondents, a number of scenarios that include the elements price, performance, and production process were created.…”
Section: Perceived Qualitymentioning
confidence: 99%